If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 35 = 11y + 2 Reorder the terms: 35 = 2 + 11y Solving 35 = 2 + 11y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11y' to each side of the equation. 35 + -11y = 2 + 11y + -11y Combine like terms: 11y + -11y = 0 35 + -11y = 2 + 0 35 + -11y = 2 Add '-35' to each side of the equation. 35 + -35 + -11y = 2 + -35 Combine like terms: 35 + -35 = 0 0 + -11y = 2 + -35 -11y = 2 + -35 Combine like terms: 2 + -35 = -33 -11y = -33 Divide each side by '-11'. y = 3 Simplifying y = 3
| .5(6x-3)=.5(6+6x) | | -(7x+10)-10=-8(4+x) | | 2(c+6)=3G-6g | | x=3x-40 | | 7b=10b+18 | | 6(-10p-3)-8p=6(-12p-3)-4 | | v^2-4v-37=2 | | 24x-3(2x-5)=51 | | 73-x=86-2x | | (2x^2-3xy^2-y^2)-(3x^2-xy^2)= | | F(X)=20(0.9)x^6 | | 6m+9+7x-2= | | 9.25x=5.75x+40 | | 8w-12=(-4) | | -10+6m-m=-1+3m+5m | | 74t+28t-101t+16=89 | | 3n-6=3-5n-n | | 5+7-9-8=11 | | -4(w+1)=-20 | | -7y+14=-28 | | 5x^2+4x=-3 | | 4x-10=3x-4 | | -540+13p=1500 | | -67a+56a=99 | | 4n^2=256 | | 4x-30=130 | | 37a-73a+73a+-33a=100 | | -2a-2=0 | | 5x-5.5=5x+26 | | x^2y+2xy-4x+y=0 | | 9c+13=58 | | 3x-4=-6x+14 |